Application of New Instruments to Increase Effectiveness of Implementation of Social Policies on Labour Market in Bulgaria - Terziev, Venelin; Arabska, Ekaterina (Journal of Economic Development, Environment and People, 2015)
Nowadays, public employment services face a number of urgent tasks as raising the employment rate and reducing the number of vacant jobs for which is difficult to find enough qualified workers. New realities on labour market and dynamic environment require adequate actions, rational and timely decision making and optimization of work. Dynamic changes in social environment impacting labour markets and activities of public employment services impose various tasks which implementation should be carefully planned, organized and controlled. To achieve that public employment services should take a more comprehensive look at the demand and supply of labour, considering the numerous transitions taking place constantly on the labour market and people's personal development. Improving processes and the quality of the administrative services in the Bulgarian employment agency is seen as a prerequisite for effective implementation of employment policies. The study presents opportunities for improving the quality of services offered in the Directorates "Labour Office" in the Republic of Bulgaria by introducing a process model and improvements in the capacity and efficiency of work in the field of labour mediation.